The Future of Pesantren: Reconciling Tradition with Global Educational Trends - Achmadin, Balya Ziaulhaq; Kawakip, Akhmad Nurul; Nafis, M. Muntahibun; Barizi, Ahmad; Asrori, Mohammad; Amrullah, Abdul Malik K. (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
The rapid social changes driven by globalization and technology demand that pesantren education adapt to remain relevant. This qualitative research analyzes the shifting goals of pesantren education in East Java, particularly in the context of the emergence of International Islamic Boarding Schools (IIBS). Using the thoughts of Zamakhsyari Dhofier and Abdurrahman Mas’ud, the study explores how IIBS impacts pesantren education, focusing on balancing tradition and modernity. The findings reveal that while IIBS enhances educational access and academic quality, it also poses risks to the preservation of pesantren's traditional values. Dhofier’s emphasis on integrating religious and secular education, combined with Mas’ud’s perspective on innovation that respects tradition, provides essential insights into this phenomenon. The study recommends a balanced approach to modernization and the preservation of Islamic values to ensure pesantren education remains effective in addressing contemporary challenges.